Differential induction of type I interferon by type I and type II feline coronaviruses in vitro. (October 2018) - Doki, Tomoyoshi; Yabe, Midori; Takano, Tomomi; Hohdatsu, Tsutomu
Abstract: Feline infectious peritonitis (FIP) is a feline coronavirus (FCoV)-induced fatal disease in wild and domestic cats. There are two FCoV serotypes. Both type I and II FCoV can replicate in Felis catus whole fetus (fcwf)-4 cells, but the replicability of type I FCoV in feline cell lines is lower than that of type II FCoV, the reason for which is unclear. Inhibition of IFNβ production by non-structural and structural proteins, excluding spike protein has been reported in many coronavirus infections. In this study, we investigated whether IFNβ is involved in the difference in replicability in feline cell lines between types I and II FCoV. When fcwf-4 cells were infected with FCoV, the virus titer of type II FCoV in the culture supernatant was higher than that of type I FIPV. When the IFNβ expression level in FCoV-infected fcwf-4 cells was semi-quantitatively analyzed, infection with type I FIPV, excluding type I FIPV UCD-1, highly induced IFNβ expression. In contrast, induction of IFNβ by type II FCoV infection was significantly lower than that by type I FIPV. In addition, when fcwf-4 cells were adsorbed by FIPV and then stimulated with Poly(I:C), type II FCoV infection inhibited Poly(I:C)-induced IFNβ gene expression. Also, the proliferation of type I FIPV was enhanced by a IFN inhibitor. These findings clarified that, unlike type I FIPV, type II FCoV strongly inhibits IFNβ expression in infected cells. It was also suggested that the IFNβ-inducing ability is different among type I FIPV strains. Highlights: Feline coronavirus is classified into 2 serotypes. Induction of IFNβ by type II FCoV infection was lower than that by type I FCoV. Type II FCoV infection inhibited Poly(I:C)-induced IFNβ gene expression. Type II FCoV strongly inhibits IFNβ expression in infected cells.